Leveraging 3D printing for advanced wound dressing technologies by using polymeric materials and polymeric biomaterials - Yogesh Jadhav; Onkar Bhingoli; Ashwin Mali; Vrushali Pawar; Vaibhav Shinde (Hybrid Advances)
The evolution of wound dressing technologies has been significantly influenced by the advent of three-dimensional (3D) printing. This review investigates the use of 3D printing to create sophisticated wound dressings with the goal of improving wound care thereby the best possible healing. Various aspects of 3D printing, including its high controllability and resolution, are discussed in the context of addressing the challenges associated with wound care. Emphasis is placed on the fabrication of tailored scaffolds using varied materials and techniques, with a focus on enhancing antibacterial properties, moisture absorption capabilities, and overall functionality. Case studies and recent advancements in the field are reviewed to illustrate the potential of 3D printing technology in revolutionizing wound dressing design and production Furthermore, the development of novel concepts like pH sensors and biocompatible parts emphasises the adaptability and customisability that 3D printing provides. Overall, this review emphasises the transformative impact of leveraging 3D printing in the development of next-generation wound dressing technologies by using polymeric materials and polymeric biomaterials, aiming to facilitate optimal wound healing and improve patient outcomes.